2014
DOI: 10.1007/s00402-014-2010-z
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of macroscopic and histologic healing of side-to-side (SS) tenorrhaphy technique and primer tendon repair in a rabbit model

Abstract: The result of the current study showed that histological healing and union of SS tenorrhaphy differ from that in primary tendon injury and healing. Further studies are required to clarify the healing stages at the tenorrhaphy site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Side-to-side repair of the tendon formed a fibrovascular sheath around the repaired tendon; however, few interdigitations were observed between the tendons. 7 Likewise, tendon-to-tendon healing seems not to occur between suture-tied supraspinatus and augmented biceps tendons. Duralde and Bair 8 documented that closing the defect of the torn rotator cuff tendon was less important in the treatment of rotator cuff tears than the re-establishment of stable fulcrum kinematics and may temporarily act as a watertight seal.…”
Section: Discussionmentioning
confidence: 99%
“…Side-to-side repair of the tendon formed a fibrovascular sheath around the repaired tendon; however, few interdigitations were observed between the tendons. 7 Likewise, tendon-to-tendon healing seems not to occur between suture-tied supraspinatus and augmented biceps tendons. Duralde and Bair 8 documented that closing the defect of the torn rotator cuff tendon was less important in the treatment of rotator cuff tears than the re-establishment of stable fulcrum kinematics and may temporarily act as a watertight seal.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, re-tear of the repaired tendon occurred in nine of 30 patients with biceps augmentation. Dogramaci et al 31 demonstrated that tendon-to-tendon healing could only be obtained from end-to-end anastomosis using a rabbit model. In other anastomosis, a thick fibrovascular sheath was formed around the anastomosis, but no healing was observed between tendon tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, tendon-to-tendon healing seems not to occur between suture-tied SP and augmented biceps tendon. 11 The present technique uses the LHBT to restrict the superior migration of the humeral head, relieving the tension over the repair of the RCT. Another differential aspect of the present technique is that a bony trough is created to fix the biceps.…”
Section: Discussionmentioning
confidence: 99%